Penatalaksanaan fisioterapi pada kondisi paska operasi medial collateral ligament knee dextra di rs al dr. ramelan surabaya - Iswamarokta, Addin Hamzahnor; Sugiono, SS t .FT (2014)
Background: The ligaments of the knee joint is also a part of the body that continues constantly under pressure while performing everyday activities. Trauma caused by accidents, falls, or a direct blow to the knee can cause injury to the ligaments at various locations on the top of the knee, above the knees, outer part of the knee or at the knee itself. The above conditions result in pain, muscle weakness, and reduced function. Purpose: To determine how the benefits of infrared therapy and exercise on pain reduction, increased muscle strength, and increased range of motion in the circumstances of the medial collateral ligament after surgery. Results : After therapy 6 times obtained results a decrease in pain, an increase in muscle strength, an increase in range of motion of active and passive right knee and an increase in functional capability. Conclusion: In the case of post surgery can be performed infrared therapy and exercise therapy. Infra red can reduce pain, spasme and exercise therapy can improve muscle strength and range of movement.